2022
DOI: 10.1108/gkmc-12-2021-0213
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use among Ukrainian and US students: a library perspective

Abstract: Purpose This study aims to determine college/university students’ mobile phone practices to understand key user preferences and set a baseline understanding for the development of prospective library informational mobile services. Design/methodology/approach This study is based on the results of an online-survey method. The authors recruited students majoring in the Information Science program in School of Information at Pratt Institute (USA) (74 participants) and in Kyiv National University of Cultural and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…Alrefaai [39] showed that EFL students use their mobile phones for academic purposes in an online learning environment, but they also face some challenges such as technical difficulties, the small size of the screen, distraction, and getting tired. Hranchak et al [40] investigated Ukrainian and USA information science students' mobile phone practices to understand participant preferences and set a baseline understanding for the development of prospective library informational mobile services. Such services may include information and reference service via messengers, development of library mobile applications of audio and video content, and access to educational, scientific, popular science literature and fiction.…”
Section: University Students' Mobile Phone Practicesmentioning
confidence: 99%
“…Alrefaai [39] showed that EFL students use their mobile phones for academic purposes in an online learning environment, but they also face some challenges such as technical difficulties, the small size of the screen, distraction, and getting tired. Hranchak et al [40] investigated Ukrainian and USA information science students' mobile phone practices to understand participant preferences and set a baseline understanding for the development of prospective library informational mobile services. Such services may include information and reference service via messengers, development of library mobile applications of audio and video content, and access to educational, scientific, popular science literature and fiction.…”
Section: University Students' Mobile Phone Practicesmentioning
confidence: 99%
“…Менш поширеними, проте надзвичайно перспективними з огляду на комунікаційні пріоритети молодіжної аудиторії [25] є бібліотечні практики реалізації проєктів зі створення відповідних бібліотечно-інформаційних мобільних застосунків, детально проаналізовані В. Бондаренко [2].…”
Section: імерсивні продуктиunclassified
“…Several studies (Duncan, 2021; Dwivedi et al , 2019; Elahi et al , 2018; Hranchak et al , 2022; Kamarianos et al , 2020; Kim et al , 2020) have been conducted to discern library user perceptions and attitudes about the usefulness of mobile technology in accessing library services at higher education institutions. According to Fan et al (2020, p. 105), Hranchak et al (2022, p. 3) and Kim et al (2020, p. 2), modern library users have positive attitudes towards mobile technology and are starting to demand libraries to provide services that are accessible via mobile technologies.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al (2021, p. 535) indicate that libraries are now offering online mobile services such as searchable Online Public Access Catalogue (OPAC), eBook and Journal downloads, quick response code, audio and video sharing accessible via mobile devices such as laptops, smartphones, iPads and mobile tablets. Several studies (Duncan, 2021; Dwivedi et al , 2019; Elahi et al , 2018; Hranchak et al , 2022; Kamarianos et al , 2020; Kim et al , 2020) have been conducted to discern library user perceptions and attitudes about the usefulness of mobile technology in accessing library services at higher education institutions. According to Fan et al (2020, p. 105), Hranchak et al (2022, p. 3) and Kim et al (2020, p. 2), modern library users have positive attitudes towards mobile technology and are starting to demand libraries to provide services that are accessible via mobile technologies.…”
Section: Introductionmentioning
confidence: 99%